(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates the regional disparities in financial awareness among farmers in Haryana and examines their effects on agricultural productivity. A comprehensive survey of 846 farmers from diverse districts was conducted to assess the levels of awareness regarding crop loans and crop insurance, and to explore how these awareness levels influence agricultural practices and productivity. Descriptive and inferential statistical analyses, including factor analysis, were employed to identify key factors contributing to these disparities and their impact. The results reveal significant variations in financial awareness across different regions, influenced by educational background, access to information, and regional economic development. Farmers with higher education and better access to information sources exhibited greater awareness of crop loans and insurance, while those in less developed areas showed lower levels of awareness. The study highlights the crucial role of government initiatives in promoting financial literacy but points out the need for more region-specific and tailored programs to address the unique challenges faced by farmers in different areas. Higher levels of financial awareness were associated with better utilization of crop loans and insurance, leading to improved agricultural practices, better risk management, and enhanced productivity. The findings underscore the importance of targeted educational programs and policy interventions to bridge the awareness gap and support sustainable agricultural growth. The study concludes that addressing regional disparities in financial awareness is essential for optimizing the use of crop loans and insurance, thereby supporting the economic well-being of farmers and the overall sustainability of the agricultural sector in Haryana.